Structural Engineering Research Frontiers 2007
DOI: 10.1061/40944(249)53
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Investigation of Partially Buckling Restrained Braces

Abstract: Although in its infancy, leveraging high strength fiber reinforced polymer (FRP) materials for retrofit of steel structures has been the focus of recent investigations. Studies include the application of FRP to steel for flexural and fatigue or fracture retrofit as well as improving steel member stability. The research presented in this thesis attempts to introduce the concept of an FRP-stabilized steel member through a retrofit application creating a Partially Buckling Restrained Brace (PBRB). A PBRB seeks to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Rahai et al [92] used PVC pipes and FRP sheets as the outer covering material and investigated such BRBs experimentally and numerically and concluded that these materials were suitable alternatives for steel. Partial BRBs were also proposed by Abraham [93]; they were made of fibre-reinforced polymerstabilized steel members through a retrofit application.…”
Section: Casing Designmentioning
confidence: 99%
“…Rahai et al [92] used PVC pipes and FRP sheets as the outer covering material and investigated such BRBs experimentally and numerically and concluded that these materials were suitable alternatives for steel. Partial BRBs were also proposed by Abraham [93]; they were made of fibre-reinforced polymerstabilized steel members through a retrofit application.…”
Section: Casing Designmentioning
confidence: 99%